2009
DOI: 10.1074/jbc.m808327200
|View full text |Cite
|
Sign up to set email alerts
|

p38α and p38γ Mediate Oncogenic ras-induced Senescence through Differential Mechanisms

Abstract: Oncogene-induced senescence is a tumor-suppressive defense mechanism triggered upon activation of certain oncogenes in normal cells. Recently, the senescence response to oncogene activation has been shown to act as a bona fide barrier to cancer development in vivo. Multiple previous studies have implicated the importance of the p38 MAPK pathway in oncogene-induced senescence. However, the contribution of each of the four p38 isoforms (encoded by different genes) to senescence induction is unclear. In the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 64 publications
5
60
1
Order By: Relevance
“…Recent studies have demonstrated that MAPK signaling pathways play a major role in regulating cell-cycle reentry and oncogenic ras-induced senescence. [39][40][41] The results of the present study show clearly that human Treg cells modulated the specific MAPK p38 and ERK1/2 signaling pathways selectively in responder T cells. In addition, our in vitro and in vivo studies suggest that specific MAPK signaling pathway inhibition in responder T cells can prevent the induction of T-cell senescence mediated by Treg cells.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Recent studies have demonstrated that MAPK signaling pathways play a major role in regulating cell-cycle reentry and oncogenic ras-induced senescence. [39][40][41] The results of the present study show clearly that human Treg cells modulated the specific MAPK p38 and ERK1/2 signaling pathways selectively in responder T cells. In addition, our in vitro and in vivo studies suggest that specific MAPK signaling pathway inhibition in responder T cells can prevent the induction of T-cell senescence mediated by Treg cells.…”
mentioning
confidence: 69%
“…39,40 It has been reported that ERK1/2 and p38 activation can induce p21-dependent G 1 cell-cycle arrest. 41 Therefore, in the present study, we investigated whether human Treg-induced naive T-cell cycle G 0 /G 1 arrest and conversion of naive CD4 ϩ T cells into senescent T cells involved MAPK signaling modulation.…”
Section: Human Treg Cells Induce the Selective Modulation Of Mapk P38mentioning
confidence: 99%
“…This hypothesis is supported by the finding that the progeny of LKS + cells cultured with SB exhibited significantly less SA-bgal staining and expression of p16 mRNA than those without SB. SA-b-gal is a widely used biomarker of senescent cells [34] and increased expression of p16 has been implicated in the induction of cellular senescence down-stream of p38 activation [26,33]. In addition, a significant fewer apoptotic cells were detected in LKS + cells cultured with SB than the cells without SB, indicating that p38 inhibition can also inhibit HSC apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which p38 inhibition promotes HSC self-renewal and ex vivo expansion may be attributable primarily to the inhibition of cellular senescence, because it has been shown that p38 functions as a key molecule mediating diverse stimuli-induced cellular senescence via upregulation of p16 in a variety of cells, including HSCs [14,15,32,33]. This hypothesis is supported by the finding that the progeny of LKS + cells cultured with SB exhibited significantly less SA-bgal staining and expression of p16 mRNA than those without SB.…”
Section: Discussionmentioning
confidence: 99%
“…These variants had acquired increased autophosphorylation activity (Fig. 6B) (13) sufficient to elevate their catalytic activities (15,18,30,31). We thus coincubated the Histagged WT or active variants of each p38 isoform with increasing amounts of their GST-tagged KD counterpart (Fig.…”
Section: P38␤mentioning
confidence: 99%